Preparation process of thick-wall single-layer PET (Polyethylene Terephthalate) bottle

Through the blending and modification of polymer chain extenders and inorganic nanoparticles with PET, combined with reaction extrusion granulation and microwave-assisted one-step injection-pull blow molding process, the problems of low production efficiency and uneven bottle wall thickness in PET bottle preparation are solved, and the preparation of high-quality thick-walled single-layer PET bottles is realized, which improves drop resistance and transparency, and reduces production costs.

CN119820825APending Publication Date: 2025-04-15JIANGYAN K K PLASTIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510041266.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing PET bottle preparation process has problems such as low production efficiency, large labor intensity and uneven bottle wall thickness, which is difficult to meet the market's demand for high-quality PET bottles.

Method used

The polymer chain extender, inorganic nanoparticles and PET are used for blending and modification, and the thick-walled single-layer PET bottle is formed through reaction extrusion granulation and microwave-assisted one-step injection-pull blow molding process. This process accelerates matrix crystallization through nanoparticle nucleation, improves crystallinity and melt viscosity, thereby enhancing bottle wall thickness and drop resistance.

Benefits of technology

The uniformity of PET bottle wall thickness is achieved, which enhances drop resistance and transparency, reduces production costs, improves production efficiency, and does not require a heat conduction process, and has high immediate operation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation process of a thick-wall single-layer PET bottle, and relates to the technical field of plastic packaging. A macromolecular chain extender, inorganic nanoparticles and PET are blended, a matrix is subjected to micro-crosslinking through reactive extrusion, the nanoparticles play a role of a nucleating agent, so that the thickness of the bottle wall of a PET bottle can be increased, the anti-falling performance is improved, then the matrix is formed through microwave-assisted one-step four-station injection-drawing blow molding, and the anti-falling performance of the PET bottle is improved. Therefore, the bottle blank obtains good temperature distribution to meet the subsequent blow molding requirement in the bottle making process, meanwhile, the uniformity of the wall thickness of the bottle blank can be enhanced, the transparency and the falling resistance of the PET bottle are improved, the bottle blank is completely blown up through high-pressure blowing to be tightly attached to the inner surface of the mold and fully formed, then demolding is conducted, and a finished bottle device is taken out. The production cost is reduced, and the product quality is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic packaging, in particular to a preparation process of a thick-walled single-layer PET bottle. Background Art

[0002] In recent years, with the continuous increase in beverage varieties, the beverage industry has developed rapidly. During the stretch blow molding process, the molecular chains of PET materials are rearranged in an orderly manner, which improves the mechanical properties and permeation barrier properties of PET bottles. PET bottles have the advantages of light weight, good transparency and recyclability, making them gradually replace glass bottles in the beverage packaging industry. With the continuous improvement of bottle blowing equipment and the continuous improvement of PET bottle stretch blow molding technology, the production cost of PET bottles has been reduced, greatly increasing the market share of PET bottles. Now PET bottles have developed into the world's most important beverage packaging form, with huge market potential.

[0003] PET, the full name of which is polyethylene terephthalate in Chinese, is one of the most widely used polymer compounds. It has good physical, optical and mechanical properties, such as light weight, good water vapor barrier, high transparency, good gloss, pressure resistance and wear resistance, high tensile strength, etc. In addition, PET materials have extremely high recycling potential. In the recycling logo formulated by the American Plastics Industry Association (PIA), PET is specified as No. 1 recycled material. In addition, PET materials are non-toxic, harmless, safe and hygienic. Compared with PE, PVC and other materials, no harmful gases are produced during combustion. Based on the above characteristics, PET has become the main material for making beverage bottles, medicine bottles and cosmetic bottles. The production of PET bottles generally adopts one-step and two-step processes. However, compared with the two-step process, the one-step process has higher production efficiency, lower labor intensity and no secondary pollution. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation process of a thick-walled single-layer PET bottle to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a preparation process of a thick-walled single-layer PET bottle, comprising the following preparation steps:

[0006] (1) The inorganic particles are dried at 80° C. and a vacuum degree of 0.2 to 1 kPa for 10 to 15 h, and then dispersed in an 80 wt% ethanol aqueous solution, ultrasonicated at 21 kHz for 50 to 100 min, KH570 is added, the temperature is raised to 65 to 90° C., stirred at 80 to 160 rpm for 10 to 12 h, centrifuged at 10,000 rpm for 5 min, filtered, and the solid is taken, washed with anhydrous ethanol for 3 to 5 times, and dried at 60 to 85° C. and a vacuum degree of 0.2 to 1 kPa for 10 to 15 h to obtain intermediate A;

[0007] (2) mixing the chain extender, PET and intermediate A, raising the temperature to 230-300° C., stirring at 80-150 rpm for 30-80 min, adding tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate and tolyl diphenyl phosphate, and extruding and granulating to obtain copolymer particles;

[0008] (3) The copolymer particles are pretreated and then subjected to microwave heating and one-step injection stretch blow molding to obtain a thick-walled single-layer PET bottle.

[0009] Furthermore, the inorganic particles in step (1) are prepared by mixing nano-silicon dioxide, nano-titanium dioxide and nano-montmorillonite in a mass ratio of 1:1:1.

[0010] Furthermore, in step (1), the mass ratio of the inorganic particles, 80 wt % ethanol aqueous solution, and KH570 is 1:80-150:0.05-0.1.

[0011] Furthermore, the chain extender in step (2) is epoxy resin E20.

[0012] Furthermore, the PET in step (2) is specifically polyethylene terephthalate with a viscosity of 0.64 to 0.83 dL / g.

[0013] Furthermore, the process parameters of the extrusion granulation in step (2) are: screw diameter of 20 mm, rotation speed of 55 rpm, aspect ratio of 25:1, extrusion temperature of 250-295° C., and shear rate of 80-150 rpm.

[0014] Furthermore, in step (2), the mass ratio of the chain extender, PET, intermediate A, tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and tolyl diphenyl phosphate is 1-2:100:4-10:0.05-0.5:0.05-0.5:0.5-1.

[0015] Furthermore, the pretreatment step in step (3) is as follows: the copolymer particles are heated to 120° C. and vacuumed every 30 minutes until there is no moisture at all.

[0016] Furthermore, the one-step process parameters of step (3) are as follows: microwave power of 800 W, heating time of 5 s, stretching speed of 1.3-1.7 m / s, delay time of 0.3-0.7, blow molding pressure of 15-20 MPa, holding time of 4-8 s, and cooling time of 5 s.

[0017] Furthermore, the thick-walled single-layer PET bottle in step (3) has a wall thickness of 3 mm and a bottom thickness of 3.5 to 4.5 mm.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention utilizes polymer chain extenders, inorganic nanoparticles and PET for blending and modification, and micro-crosslinking of the matrix is ​​generated by reactive extrusion, wherein the nanoparticles act as nucleating agents, which can not only accelerate the crystallization rate of the matrix and improve the crystallinity, but also increase the melt viscosity, thereby enhancing the thickness of the PET bottle wall and improving the drop resistance. Subsequently, the matrix is ​​formed by microwave-assisted one-step four-station injection stretch blow molding, and the microwave device has a good electric field distribution, so that the preform obtains a good temperature distribution to meet the requirements of bottle making. The subsequent blow molding requirements in the process can also enhance the uniformity of the wall thickness of the preform, improve the transparency and drop resistance of the PET bottle, and no heat conduction process is required during heating, and the thermal inertia is small. Only the microwave power needs to be adjusted to quickly heat the material to the appropriate temperature. There is no "waste heat" and it has high instant operability. The heating effect of the preform is improved from the heating essence, thereby improving the production efficiency of bottle making. The preform is then completely inflated and close to the inner surface of the mold through high-pressure blowing, fully formed, and then demolded to take out the finished bottle, so that the product is in place in one step, which not only reduces production costs but also improves product quality. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0020] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the thick-walled single-layer PET bottles prepared in the following examples are as follows:

[0021] Transparency: The light transmittance of each embodiment and comparative example was tested according to GB / T2410.

[0022] Drop resistance: The cantilever beam notched impact strength of each embodiment and comparative example was tested according to GB / T1843.

[0023] Example 1

[0024] (1) Nano-silicon dioxide, nano-titanium dioxide and nano-montmorillonite are mixed in a mass ratio of 1:1:1 to obtain inorganic particles; the inorganic particles are dried at 80° C. and a vacuum degree of 0.2 kPa for 10 h, and then dispersed in an 80 wt% ethanol aqueous solution, ultrasonicated at 21 kHz for 50 min, KH570 is added, the temperature is raised to 65° C., stirred at 80 rpm for 10 h, centrifuged at 10000 rpm for 5 min, filtered, the solid is taken, washed with anhydrous ethanol for 3 times, and dried at 60° C. and a vacuum degree of 0.2 kPa for 10 h to obtain an intermediate A; the mass ratio of the inorganic particles, the 80 wt% ethanol aqueous solution and KH570 is 1:80:0.05;

[0025] (2) Epoxy resin E20, polyethylene terephthalate with a viscosity of 0.64 dL / g, and intermediate A were mixed, heated to 230°C, stirred at 80 rpm for 30 min, and tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and tolyl diphenyl phosphate were added for extrusion granulation. The process parameters were: screw diameter of 20 mm, rotation speed of 55 rpm, and long diameter of 1.5 mm. The ratio is 25:1, the extrusion temperature is 250°C, and the shear rate is 80rpm to obtain copolymer particles; the mass ratio of the epoxy resin E20, polyethylene terephthalate with a viscosity of 0.64dL / g, intermediate A, tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and tolyl diphenyl phosphate is 1:100:4:0.05:0.05:0.5;

[0026] (3) The copolymer particles were dried at 120°C for 4 h, during which vacuum was drawn every 30 min until there was no water present. The particles were then heated by microwave and subjected to one-step injection stretch blow molding. The process parameters were as follows: microwave power of 800 W, heating time of 5 s, stretching speed of 1.3 m / s, delay time of 0.3, blow molding pressure of 15 MPa, holding time of 4 s, and cooling time of 5 s. A thick-walled single-layer PET bottle with a wall thickness of 3 mm and a bottom thickness of 3.5 mm was obtained.

[0027] Example 2

[0028] (1) Nano-silicon dioxide, nano-titanium dioxide and nano-montmorillonite are mixed in a mass ratio of 1:1:1 to obtain inorganic particles; the inorganic particles are dried at 80° C. and a vacuum degree of 0.6 kPa for 12 h, and then dispersed in an 80 wt% ethanol aqueous solution, ultrasonicated at 21 kHz for 60 min, KH570 is added, the temperature is raised to 80° C., stirred at 120 rpm for 11 h, centrifuged at 10000 rpm for 5 min, filtered, the solid is taken, washed with anhydrous ethanol for 4 times, and dried at 70° C. and a vacuum degree of 0.6 kPa for 12 h to obtain an intermediate A; the mass ratio of the inorganic particles, the 80 wt% ethanol aqueous solution and KH570 is 1:110:0.08;

[0029] (2) Epoxy resin E20, polyethylene terephthalate with a viscosity of 0.73 dL / g, and intermediate A were mixed, heated to 260°C, stirred at 120 rpm for 50 min, and tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and tolyl diphenyl phosphate were added for extrusion granulation. The process parameters were: screw diameter of 20 mm, rotation speed of 55 rpm, and long diameter of 1.5 mm. The ratio is 25:1, the extrusion temperature is 275°C, and the shear rate is 120rpm to obtain copolymer particles; the mass ratio of the epoxy resin E20, polyethylene terephthalate with a viscosity of 0.73dL / g, intermediate A, tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and tolyl diphenyl phosphate is 1.5:100:7:0.2:0.3:0.8;

[0030] (3) The copolymer particles were dried at 120°C for 6 h, during which vacuum was drawn every 30 min until there was no water present. The particles were then heated by microwave and subjected to one-step injection stretch blow molding. The process parameters were as follows: microwave power of 800 W, heating time of 5 s, stretching speed of 1.5 m / s, delay time of 0.5, blow molding pressure of 18 MPa, holding time of 6 s, and cooling time of 5 s. A thick-walled single-layer PET bottle with a wall thickness of 3 mm and a bottom thickness of 4 mm was obtained.

[0031] Example 3

[0032] (1) Nano-silicon dioxide, nano-titanium dioxide and nano-montmorillonite are mixed in a mass ratio of 1:1:1 to obtain inorganic particles; the inorganic particles are dried at 80° C. and a vacuum degree of 1 kPa for 15 h, and then dispersed in an 80 wt% ethanol aqueous solution, ultrasonicated at 21 kHz for 100 min, KH570 is added, the temperature is raised to 90° C., stirred at 160 rpm for 12 h, centrifuged at 10000 rpm for 5 min, filtered, the solid is taken, washed with anhydrous ethanol for 5 times, and dried at 85° C. and a vacuum degree of 1 kPa for 15 h to obtain an intermediate A; the mass ratio of the inorganic particles, the 80 wt% ethanol aqueous solution and KH570 is 1:150:0.1;

[0033] (2) Epoxy resin E20, polyethylene terephthalate with a viscosity of 0.83 dL / g, and intermediate A were mixed, heated to 300°C, stirred at 150 rpm for 80 min, tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and tolyl diphenyl phosphate were added, and extrusion granulation was performed. The process parameters were: screw diameter of 20 mm, rotation speed of 55 rpm, The aspect ratio is 25:1, the extrusion temperature is 295°C, and the shear rate is 150rpm to obtain copolymer particles; the mass ratio of the epoxy resin E20, polyethylene terephthalate with a viscosity of 0.83dL / g, intermediate A, tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and tolyl diphenyl phosphate is 2:100:10:0.5:0.5:1;

[0034] (3) The copolymer particles were dried at 120°C for 8 h, during which vacuum was drawn every 30 min until there was no water present. The particles were then heated by microwave and subjected to one-step injection stretch blow molding. The process parameters were as follows: microwave power of 800 W, heating time of 5 s, stretching speed of 1.7 m / s, delay time of 0.7, blow molding pressure of 20 MPa, holding time of 8 s, and cooling time of 5 s. A thick-walled single-layer PET bottle with a wall thickness of 3 mm and a bottom thickness of 4.5 mm was obtained.

[0035] Comparative Example 1

[0036] The difference between Comparative Example 1 and Example 2 is that step (2) is different. Step (2) is changed to: polyethylene terephthalate with a viscosity of 0.73 dL / g and intermediate A are mixed, the temperature is raised to 260° C., and tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and tolyl diphenyl phosphate are added with stirring at 120 rpm for 50 min, and extrusion granulation is performed. The process parameters are: screw diameter is 20 mm, The rotation speed is 55 rpm, the aspect ratio is 25:1, the extrusion temperature is 275°C, and the shear rate is 120 rpm to obtain copolymer particles; the mass ratio of the polyethylene terephthalate with a viscosity of 0.73 dL / g, the intermediate A, tris(2,4-di-tert-butylphenyl) phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, and tolyl diphenyl phosphate is 100:7:0.2:0.3:0.8; the remaining steps are the same as in Example 2.

[0037] Comparative Example 2

[0038] The difference between Comparative Example 2 and Example 2 is that there is no step (1), and step (2) is changed to: epoxy resin E20 and polyethylene terephthalate with a viscosity of 0.73 dL / g are mixed, the temperature is raised to 260°C, and tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and tolyl diphenyl phosphate are added for extrusion granulation. The process parameters are: screw diameter 20 mm, rotation speed 2000 rpm, and rotation speed 2000 rpm. The speed is 55 rpm, the aspect ratio is 25:1, the extrusion temperature is 275°C, and the shear rate is 120 rpm to obtain copolymer particles; the mass ratio of the epoxy resin E20, polyethylene terephthalate with a viscosity of 0.73 dL / g, tris(2,4-di-tert-butylphenyl) phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, and tolyl diphenyl phosphate is 1.5:100:0.2:0.3:0.8; and the remaining steps are the same as in Example 2.

[0039] Comparative Example 3

[0040] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: epoxy resin E20, polyethylene terephthalate with a viscosity of 0.73 dL / g, intermediate A, tris(2,4-di-tert-butylphenyl) phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, and tolyl diphenyl phosphate are mixed, the temperature is raised to 260° C., and stirred at 120 rpm for 50 min. After shearing, copolymer particles are obtained; the mass ratio of the epoxy resin E20, polyethylene terephthalate with a viscosity of 0.73 dL / g, intermediate A, tris(2,4-di-tert-butylphenyl) phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, and tolyl diphenyl phosphate is 1.5:100:7:0.2:0.3:0.8; the remaining steps are the same as Example 2.

[0041] Comparative Example 4

[0042] The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: the copolymer particles are dried at 120° C. for 6 h, and vacuum is drawn every 30 min during this period until there is no water at all, and then they are formed by one-step injection stretch blow molding. The process parameters are as follows: temperature of 265° C., stretching speed of 1.5 m / s, delay time of 0.5, blow molding pressure of 18 MPa, holding time of 6 s, cooling time of 5 s, to obtain a thick-walled single-layer PET bottle with a bottle wall thickness of 3 mm and a bottle bottom thickness of 4 mm. The remaining steps are the same as those of Example 2.

[0043] Effect example

[0044] Table 1 below shows the performance analysis results of the thick-walled single-layer PET bottles using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0045] Table 1

[0046] Light transmittance (%) <![CDATA[Izod impact strength of cantilever beam (kJ / m 2 )]]> Example 1 93.1 6.18 Example 2 93.8 6.27 Example 3 92.9 6.22 Comparative Example 1 91.5 5.73 Comparative Example 2 91.7 4.96 Comparative Example 3 92.2 5.49 Comparative Example 4 92.4 5.81

[0047] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention utilizes polymer chain extenders, inorganic nanoparticles and PET for blending and modification, and the matrix is ​​micro-crosslinked by reactive extrusion, wherein the nanoparticles act as nucleating agents, which can not only accelerate the crystallization rate of the matrix and improve the crystallinity, but also increase the melt viscosity, thereby enhancing the thickness of the PET bottle wall and improving the drop resistance. Then, the matrix is ​​formed by microwave-assisted one-step four-station injection stretch blow molding, and the preform obtains a good temperature distribution to meet the subsequent blow molding requirements in the bottle making process, and at the same time can enhance the uniformity of the wall thickness of the preform, improve the transparency and drop resistance of the PET bottle, and improve the effect of heating the preform from the heating essence, thereby improving the production efficiency of bottle making.

[0048] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A process for preparing a thick-walled single-layer PET bottle, characterized in that: The method comprises the following preparation steps: (1) The inorganic particles are dried at 80° C. and a vacuum degree of 0.2 to 1 kPa for 10 to 15 h, and then dispersed in an 80 wt% ethanol aqueous solution, ultrasonicated at 21 kHz for 50 to 100 min, KH570 is added, the temperature is raised to 65 to 90° C., stirred at 80 to 160 rpm for 10 to 12 h, centrifuged at 10,000 rpm for 5 min, filtered, and the solid is taken, washed with anhydrous ethanol for 3 to 5 times, and dried at 60 to 85° C. and a vacuum degree of 0.2 to 1 kPa for 10 to 15 h to obtain intermediate A; (2) mixing the chain extender, PET and intermediate A, raising the temperature to 230-300° C., stirring at 80-150 rpm for 30-80 min, adding tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate and tolyl diphenyl phosphate, and extruding and granulating to obtain copolymer particles; (3) The copolymer particles are pretreated and then subjected to microwave heating and one-step injection stretch blow molding to obtain a thick-walled single-layer PET bottle.

2. The process for preparing a thick-walled single-layer PET bottle according to claim 1, characterized in that: The inorganic particles in step (1) are prepared by mixing nano silicon dioxide, nano titanium dioxide and nano montmorillonite in a mass ratio of 1:1:

1.

3. The process for preparing a thick-walled single-layer PET bottle according to claim 1, characterized in that: The mass ratio of the inorganic particles, 80wt% ethanol aqueous solution and KH570 in step (1) is 1:80-150:0.05-0.

1.

4. The process for preparing a thick-walled single-layer PET bottle according to claim 1, characterized in that: The chain extender in step (2) is epoxy resin E20.

5. The process for preparing a thick-walled single-layer PET bottle according to claim 1, characterized in that: The PET in step (2) is specifically polyethylene terephthalate with a viscosity of 0.64 to 0.83 dL / g.

6. The process for preparing a thick-walled single-layer PET bottle according to claim 1, characterized in that: The process parameters of the extrusion granulation in step (2) are: screw diameter of 20 mm, rotation speed of 55 rpm, aspect ratio of 25:1, extrusion temperature of 250-295° C., and shear rate of 80-150 rpm.

7. The process for preparing a thick-walled single-layer PET bottle according to claim 1, characterized in that: The mass ratio of the chain extender, PET, intermediate A, tris(2,4-di-tert-butylphenyl)phosphite, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate and tolyl diphenyl phosphate in step (2) is 1-2:100:4-10:0.05-0.5:0.05-0.5:0.5-1.

8. The process for preparing a thick-walled single-layer PET bottle according to claim 1, characterized in that: The pretreatment step of step (3) is as follows: the copolymer particles are heated to 120° C. and vacuumed every 30 minutes until there is no moisture at all.

9. The process for preparing a thick-walled single-layer PET bottle according to claim 1, characterized in that: The one-step process parameters of step (3) are as follows: microwave power of 800 W, heating time of 5 s, stretching speed of 1.3-1.7 m / s, delay time of 0.3-0.7, blow molding pressure of 15-20 MPa, holding time of 4-8 s, and cooling time of 5 s.

10. The process for preparing a thick-walled single-layer PET bottle according to claim 1, characterized in that: The thick-walled single-layer PET bottle in step (3) has a wall thickness of 3 mm and a bottom thickness of 3.5 to 4.5 mm.